Program Dukungan Pendidikan Integratif bagi Mahasiswa Lamban Belajar melalui Program Adaptive E-Learning FEBUMP: Integrative Education Support Program for Slow Learners through the Adaptive E-Learning FEBUMP Program - Endratno, Hermin; Fuad, Muhammad; Randikaparsa, Irawan; Handayani, Erna; Zamakhsyari, Luthfi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The critical value of inclusive education is the creation of friendly learning for all students, both regular and children with special needs. The campus does not discriminate against students; all students are entitled to the same educational services. For that we need a program that helps learning. The aim is to support the learning success of slow learners, improve the quality and skills of lecturers in the teaching and learning process to support the learning success of slow learners, and provide supporting facilities for academic activities in the form of the FEBUMP Adaptive e-learning program for students to make it easier to understand the material and consult with psychologists. The method used is creating the FEBUMP Adaptive e-learning program, applied to lecturers, psychologists, and students. The results obtained are that lecturers get convenience and understanding in overcoming slow learners; students find it helpful in understanding the material and conducting counseling on the problem of slow learners; teaching and learning activities in the case of slow learners can be handled correctly and adequately without disturbing students who are not slow learners. In conclusion, this program is beneficial in creating a fair and inclusive education system.